Nutritional anti-nutritional chemical composition and antioxidant activities of the leaves of the sea cliff dwelling species Limonium spathulatum (Desf.) Kuntze - Youssef, Seria; Custódio, Luísa; Rodrigues, Maria João; Pereira, Catarina G.; Calhelha, Ricardo C.; Pinela, José; Barros, Lillian; Jekő, József; Cziáky, Zoltán; Ben Hamed, Karim (Frontiers in Plant Science, 2022)
This work explored the nutritional and antioxidant properties of the leaves of the halophytic species Limonium spathulatum (Desf.) Kuntze from Tunisian sea cliffs. Furthermore, the analysis of the total phenolics and flavonoids contents and their individual compounds using high-performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC-ESI-MS/MS) were also studied. L. spathulatum leaves had high levels of moisture, ash, neutral detergent fiber, and acid detergent fiber, but low concentrations of crude protein, crude fat and acid detergent lignin. It contained low carbohydrates levels, and low energetic values. The most abundant macroelements were Cl, Na and Ca while the microelements detected in the highest levels were Fe and Zn. No relevant α-amylase inhibition was observed, and no toxic metals (Pb and Cd) and phytic acid were detected. The ethanol and the hydroethanolic extracts had the highest capacity to scavenge free radicals, to chelate iron and copper and to inhibit lipid peroxidation. The same samples were also the most active towards oxidative haemolysis. These extracts contained high total phenolic and flavonoid contents. HPLC analysis, performed on ethanolic extracts identified 58 individual compounds known for their high antioxidant actvitiy including hydroxybenzoic acids (gallic, syringic acids), hydroxycinnamic acids (caffeic, coumaric, ferulic acids) and flavonoids (catechin, epigallocatechin gallate and naringin).In conclusion, the leaves of Tunisian accession of L. spathulatum were good source of minerals and fibers useful in the human diet for attaining nutritional sufficiency. The high in vitro and ex vitro antioxidant activities associated with high favonoids contents and compounds suggest the possibility to use the extracts of L. spathulatum in herbal products with the aim of improving general health and well-being, and/or as food additives for preventing lipid oxidation of lipid-rich foods.